Optical spectroscopy and dielectric properties of phosphate-tellurite glasses. (6th February 2020) - Polosan, S; Nitescu, A; Secu, M
Abstract: Tellurium metallic colloids were evidence in the phosphate tellurite glasses obtained by the melt quenching method over 1000 °C. The concentration and subsequent color of these glasses strongly depend on the preparation conditions due to the significant differences among the melting point of the component oxides. The presence of Te metallic colloids was evidenced by the magneto-optical measurements at different temperatures, by the shift of the emissions spectra with the excitation wavelength and the thermoluminescence spectra as a result of recombination between the hole centers, created during x-ray irradiation, with the quasi coupled electrons from the surface of the metallic colloids. The peak position in the absorption spectra of these metallic colloids was modeled based on generalized Mie light scattering theory on these metallic structures, taking into account the size and shape of colloids but also the dielectric constant of the phosphate tellurite glasses in which these colloids are embedded.